Interannual variation of the East Asia Jet Stream and its impact on the horizontal distribution of aerosol in boreal spring. (15th February 2020) - Lee, Seunghee; Lee, Myong-In; Song, Chang-Keun; Kim, Kyu-Myong; da Silva, Arlindo M.
Abstract: Interannual variation of the aerosol optical depth (AOD) in East Asia has been investigated using Moderate Resolution Imaging Spectroradiometer (MODIS) data and Modern Era Retrospective analysis for Research and Applications Version 2 (MERRA-2) data for 2000–2018. The data analysis focuses on boreal spring when Siberian biomass burning is at its seasonal maximum. The results indicate that the significant increase in organic and black carbon is primarily caused by emissions from biomass burning in East Asia, which leads to significant interannual variations in aerosol loading and pan-Pacific transport. The anomalous large-scale climate variability associated with the East Asia Jet Stream (EAJS) provides favorable conditions for increasing the AOD of organic and black carbon in Northeast Asia and may represent an underlying physical mechanism. When the EAJS shows greater weakening than normal, abnormal high-pressure anomalies are maintained in East Asia, which tend to drive warm advection over Northeast Asia. This warm advection expedites the melting of the Eurasian snow cover, which helps increase surface dryness in late spring and provides favorable conditions for biomass burning. The EAJS index can be predictable with statistical significance up to lead 1 month by the dynamical ensemble seasonal forecasts, suggesting a possible implementation of the empirical AOD forecasts using climate forecast models. Highlights: Interannual variation of the aerosol concentration in East Asia is investigated. Increase in biomass burning is driven by the weakening of the jet stream. High pressure and warm anomalies expedite snow melting and dry surface condition. The jet stream variability is predictable up to lead 1 month by the climate model.